Retinoblastoma in patients with 13q deletion syndrome – case series - Jędrychowska-Jamborska, Justyna; Morawski, Krzysztof; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Deletion of the long arm of chromosome 13 (13q deletion syndrome) is very rare chromosomal aberration which causes mental retardation and multiple congenital malformations. Furthermore, it is associated with the increased risk of retinoblastoma. The aim of the paper was to present two cases of retinoblastoma in children with 13q deletion syndrome, discussing the diagnostic and therapeutic management, clinical manifestation and the importance of genetic testing which helps to determine the type of retinoblastoma and may also contribute to the diagnosis of other congenital abnormalities associated with intraocular tumors.